Psychosocial and mental health challenges facing perinatally HIV-infected adolescents along the Kenyan coast: a qualitative inquiry using the socioecological model - Wanjala, Stanley W.; Nyongesa, Moses K.; Luchters, Stanley; Abubakar, Amina (Frontiers in Public Health, 2024)
The advent of antiretroviral therapy has led perinatally HIV-infected (PHI) adolescents to live long, fulfilling lives through lifelong treatment. Still, there is limited knowledge about the lived experiences and psychosocial and mental health challenges faced by PHI adolescents in sub-Saharan Africa, where eighty percent of PHI adolescents reside. To address this gap, we adapted the socioecological model to investigate the challenges and lived experiences of PHI adolescents in rural coastal Kenya.Methods: Between October and November 2018, a convenience sample of 40 participants (20 PHI adolescents and their 20 primary caregivers) participated in a qualitative study using an H-assessment data collection approach for adolescents and focus group discussions with caregivers. Data analysis was conducted using a framework approach on NVIVO 11 software.Results: PHI adolescents from this setting experience many challenges across various levels of the ecosystem. At the individual level, reported challenges include living in denial, HIV status disclosure, antiretroviral adherence, internalized stigma, and mental health issues. Within the family, challenges involve parental loss, insufficient care from parents, and unacceptance, leading to threats of harm. In the broader community, key challenges include gossip, unsupportive community members, lengthy waiting times at the health facility, isolation, rejection, and an unresponsive school system that fails to address the needs of PHI adolescents. Finally, HIV-related stigma and discrimination manifested across different levels of the socio-ecological framework. To cope with these challenges, PHI adolescents often rely on secrecy and social support from their families.Findings underscore the need to develop and implement multi-level adolescent-friendly interventions to address PHI adolescent challenges and guide future investment in adolescent health. Furthermore, there is a need to address internalized and interpersonal stigmas through individual-level interventions that promote resilience and the active involvement of adolescents, their caregivers, peers' and teachers who are their social support system.